Pengelolaan Penggunaan Lahan untuk Stabilisasi Tepian Hutan Tropis Menggunakan Agent-Based Land-Use Modelling - Suria Darma Tarigan; Kerstin Wiegand (Jurnal Ilmu Pertanian Indonesia, 2012)
Tropical forest margin conversion to agriculture land in in Lore Lindu National Park has reached an alaming rate. The conversion was trigered by insufficient revenue to support minimal living standard amounted to                  Rp15.000.000,00/year/household obtained from unproductive cacao farming. Each household required another 1 ha new land to at least reach that minimal living standard. Therefore 218 ha of forest land are potentially cleared by farmerin the near future to extend their farming area. Increasing productivity using innovative agro-technolgy should be considered as one important alternative to reduce the need to clear another forest area. Due to the complexity of interrelated variable affected by using innovative agro-technolgy, a model should be used to take account every affected variable such as availability of labour and liquidity in adopting new agro-technology. In this research, agent-based modeling with mixed integer linear programming model (MILP) using MPMAS software (Mathematical Programming for Multy Agent System) was used to analyze impact of balanced fertilizing and irrigation technology to increase cacao land productivity. Balanced fertilizing was insufficient to reach minimum standard living of Rp15.000.000,00 with existing area of cacao land (1 ha/HH), due to the severe water deficit during month of January until February. Combining balanced fertilizing with irrigation water supply can increase productivity reaching minimum standard of living. It was obvious from the modeling that in the ealier period of cacao growth (1-5 year old), deficits in liquidity and labour was encountered. Interplanting cacao with maize at the earlier phase with additional income from livestock can alleviate liquidity shortage.